2017
DOI: 10.1002/erv.2514
|View full text |Cite
|
Sign up to set email alerts
|

Chances and Limitations of Video Games in the Fight against Childhood Obesity—A Systematic Review

Abstract: Using video games for weight management exclusively does not deliver satisfying results. Video games as an additional guided component of prevention and treatment programs have the potential to increase compliance and thus enhance treatment outcome. Copyright © 2017 John Wiley & Sons, Ltd and Eating Disorders Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 92 publications
1
35
0
1
Order By: Relevance
“…Systematic reviews have shown that AVGs have a positive impact on the social life of children and adolescents, as active games have a recreational and socialization approach [39]. Studies claim that some exergames offer a unique and exciting opportunity for positive effects on social interaction and cooperation in this audience [17,21]. Specifically, in adolescence, it is known that an important issue is social relationships and what makes this aspect very difficult is the need for isolation at home, causing frustration, nervousness, discontent, nostalgia and boredom because of social distancing [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews have shown that AVGs have a positive impact on the social life of children and adolescents, as active games have a recreational and socialization approach [39]. Studies claim that some exergames offer a unique and exciting opportunity for positive effects on social interaction and cooperation in this audience [17,21]. Specifically, in adolescence, it is known that an important issue is social relationships and what makes this aspect very difficult is the need for isolation at home, causing frustration, nervousness, discontent, nostalgia and boredom because of social distancing [48].…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that the use of active video games (AVGs), including electronic motion games, contribute to increasing daily caloric expenditure, interaction and social support, and can be used as strategies for coping with the low level of physical activity of young people during the pandemic [17][18][19]. Thus, studies with the use of interactive video games have begun to be conducted in order to use technology to "break" from the sedentary lifestyle [20][21][22][23] by performing physical activities with light to moderate intensity, encouraging and increasing energy expenditure [24,25]. In this way, in a context of social distancing, which requires commitment to take care of one's health with adequate daily habits, active games can be an interesting alternative to provide greater mental health, increase physical activity and family interaction.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review showed that most studies achieved positive results using video games in the prevention and treatment of obesity in children and adolescents. The authors emphasized that video games provide an additional and supporting element in preventing and treating obesity along with the potential to increase treatment compliance and to promote success [22]. The “Alien Health Game,” a nutrition instruction game, increased short-term nutrition knowledge among primary school children [13].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, health education linked to schools is also a good alternative. Schools would benefit from incorporating serious games into their curricula, making it more attractive to students and approximating children to technology on their daily routine 38 .…”
Section: Discussionmentioning
confidence: 99%